Design and implementation on remote disaster recovery system based on Goldengate - Zhengyu MI (Dianxin kexue)
As telecom business-critical systems become more and more important,the demand for IT classes has also increased.The IT system should be more reliable,faster and easier to use and to adapt better to changing business needs.On the other hand,the security risks are also increasing.The concept of synchronous replication technology and the realization theory of Goldengate was focused on,the characteristics and advantages of the technology were discussed.Through the analysis of actual cases,the feasibility of using Goldengate data replication technology was verified,the data real-time backup was realized,the core database security was ensured while avoiding the introduction of too many categories software,and the complexity of operation and cost inputs was reduced,also it is conducive to the recovery of disaster recovery system and real-time switching.